DAMPAK PENGGUNAAN SMARTPHONE DALAM MENINGKATKAN KUALITAS PEMBELAJARAN PENDIDIKAN AGAMA ISLAM PADA PESERTA DIDIK DI MAN 2 KOTA SUKABUMI - Amelia Putri; Ari Maulana Ibrahim; Arpi Salas; Amelia Oktaviani; Dea Fauzia; Mochammad Agung Sobandi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the impact of smartphone usage in improving the quality of Islamic Religious Education (PAI) learning among students at MAN 2 Kota Sukabumi. The rapid development of technology has made smartphones an integral part of students’ daily lives, including in the learning process. However, their use presents both opportunities and challenges in enhancing learning quality. This research aims to describe how smartphones are utilized in PAI learning and to analyze their impact on the quality of the learning process. This study employs a qualitative approach with a field research method. Data were collected through observation, interviews, and documentation involving teachers and students. The findings reveal that smartphone usage positively contributes to improving learning quality, particularly in terms of students’ understanding, engagement, and motivation. Learning becomes more interactive, flexible, and student-centered. However, challenges such as distraction, limited supervision, and varying digital competencies among students were also identified. Therefore, proper management and guidance from teachers are essential to ensure that smartphone use effectively supports learning objectives. Overall, smartphones can serve as an effective learning medium in enhancing the quality of Islamic Religious Education when used appropriately and purposefully